Head trauma in sports – clinical characteristics, epidemiology and biomarkers. (18th December 2018) - Zetterberg, H.; Winblad, B.; Bernick, C.; Yaffe, K.; Majdan, M.; Johansson, G.; Newcombe, V.; Nyberg, L.; Sharp, D.; Tenovuo, O.; Blennow, K.
Abstract: Traumatic brain injury (TBI) is clinically divided into a spectrum of severities, with mild TBI being the least severe form and a frequent occurrence in contact sports, such as ice hockey, American football, rugby, horse riding and boxing. Mild TBI is caused by blunt nonpenetrating head trauma that causes movement of the brain and stretching and tearing of axons, with diffuse axonal injury being a central pathogenic mechanism. Mild TBI is in principle synonymous with concussion; both have similar criteria in which the most important elements are acute alteration or loss of consciousness and/or post‐traumatic amnesia following head trauma and no apparent brain changes on standard neuroimaging. Symptoms in mild TBI are highly variable and there are no validated imaging or fluid biomarkers to determine whether or not a patient with a normal computerized tomography scan of the brain has neuronal damage. Mild TBI typically resolves within a few weeks but 10–15% of concussion patients develop postconcussive syndrome. Repetitive mild TBI, which is frequent in contact sports, is a risk factor for a complicated recovery process. This overview paper discusses the relationships between repetitive head impacts in contact sports, mild TBI and chronic neurological symptoms. What are these conditions, how common are they, how are they linked and can they be objectified using imaging or fluid‐based biomarkers? It gives an update on the current state of research on these questions with a specific focus on clinical characteristics, epidemiology and biomarkers. Abstract : Content List ‐ Read more articles from the symposium: "Head Trauma in Sports and Risk for Dementia".